2006
DOI: 10.1061/(asce)1090-0268(2006)10:5(433)
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Fatigue Behavior of Reinforced Concrete Beams Strengthened with FRP Fabric and Precured Laminate Systems

Abstract: Rehabilitation of existing structures with carbon fiber reinforced polymers ͑CFRP͒ has been growing in popularity because they offer resistance to corrosion and a high stiffness-to-weight ratio. This paper presents the flexural strengthening of seven reinforced concrete ͑RC͒ beams with two FRP systems. Two beams were maintained as unstrengthened control samples. Three of the RC beams were strengthened with CFRP fabrics, whereas the remaining two were strengthened using FRP precured laminates. Glass fiber ancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 7 publications
1
40
0
3
Order By: Relevance
“…Experimental evidence was also gained from strengthened RC beams with rectangular cross-sections (Lamanna et al, 2001(Lamanna et al, , 2004aMartin and Lamanna, 2008) and tee crosssections (Lamanna et al, 2004b), where fasteners were mounted using different layouts to evaluate their efficiency. Comparative experimental studies (Ekenel et al, 2006;Quattlebaum et al, 2005) on the static and fatigue performance of RC beams strengthened with MF-and EB-FRP laminates, as well as NSM FRP strips, showed that similar strength levels can be attained.…”
Section: Introductionmentioning
confidence: 94%
“…Experimental evidence was also gained from strengthened RC beams with rectangular cross-sections (Lamanna et al, 2001(Lamanna et al, , 2004aMartin and Lamanna, 2008) and tee crosssections (Lamanna et al, 2004b), where fasteners were mounted using different layouts to evaluate their efficiency. Comparative experimental studies (Ekenel et al, 2006;Quattlebaum et al, 2005) on the static and fatigue performance of RC beams strengthened with MF-and EB-FRP laminates, as well as NSM FRP strips, showed that similar strength levels can be attained.…”
Section: Introductionmentioning
confidence: 94%
“…Only in a few cases, instead, the mechanically fastening was performed by using wedge anchors [5,20,22]; in [20,22], they were installed into the concrete by using epoxy resin as a gap filler. In the case of the specimen M-F-P-2 [22], the FRP laminate was both bonded and mechanically fastened to the concrete substrate.…”
Section: The Databasementioning
confidence: 99%
“…All of beams survived fatigue testing. The result showed that the use of anchor spikes in fabric strengthening increase ultimate strength and mechanical fasteners can be an alternative to epoxy bonded laminate systems [5]. So, from all of references above, it is clear that there is a need to develop the study on ruptured concrete beams strengthened by using GFRP -S. Fig.…”
Section: Introductionmentioning
confidence: 97%